Avaliação da suscetibilidade de Candida spp. isoladas de candidemias: um estudo de 15 anos - Santos, Edileusa Rosa dos (2012)
In the last two decades it has been seen a large increase in blood stream infections by Candida spp. The candidemias are associated with high morbidity and mortality, as well as the increase in hospital costs. The phenomenon of resistance highlights the importance of performing tests for susceptibility to antifungal agents. Such tests are improving constantly in an attempt to standardize their interpretations. This study evaluated the susceptibility of Candida spp. isolated from candidemias during a period of 15 years divided into three periods of five years in Santa Maria, RS, Brazil, interpreting minimum inhibitory concentrations according to the proposal of the CLSI and the new breakpoints recently proposed by Pfaller et al. Among the 525 isolates during the three periods, C. parapsilosis was the predominant species (49.14%), followed by C. albicans (34.47%), C. tropicalis (8.19%), C. glabrata (3.61%), C. lusitaniae (1.90%), C. guilliermondii (1.71%) and C.krusei (0.95%). During the study period and considering the two criteria, 136 non-susceptible isolates were found. According to CLSI, we identified 40 (7.61%) non-susceptible isolates, from wich 19 (3.61%) were resistant. According to Pfaller et al., 96 (18.28%) isolates presented themselves as nonsusceptible, being 11 (2.09%) resistant. All isolates were susceptible to amphotericin B and 3 presented themselves dose-dependent or intermediate suscpetible to flucytosine and caspofungin. Resistance was detected only among the azole antifungals: itraconazole (2.09%), fluconazole (1.14%) and voriconazole (0.38%). The isolation of species resistant to the antifungal agents used was not a prominent feature in this study. Detecting a higher number of non-susceptible species highlighted the relevance of evaluating of susceptibility tests by new breakpoints in order to find a more efficient therapy.